PREVENTION OF SUICIDE, NEW HORIZONTS - Borokhov, A.; Borokhov, B. (Modern Psychology, 2021)
The article presents a conceptual model for assessing suicidal activity and risk, developed by the authors. This model is compiled taking into account the expanded and supplemented bio-psycho-social model of Georg Engel (Engel G., 1977), which consists of three types of constructs: biological, psychological and social. Actually, the constitutional psychotype of a person is the genetic predisposition of each specific person belonging to one of three somatotypes (normostenic, asthenic, hypersthenic) and the expected basic individual behavioral response (Fight –Flight –Freeze), which is almost always manifested in response to a stressful situation. In clinical psychology, it is generally accepted that almost any individual who is truly engulfed in suicidal thoughts, neither only does not have, but does not seek an alternative solution. Figuratively speaking, he develops "tunnel vision", that is, he sees a very minimal range of solutions to his problem, more precisely one - fatal. Therefore, we came to the conclusion that it is necessary to create a system of "external and internal anchors" that keep the patient from committing a suicidal act. Therefore, we came to the conclusion that it is necessary to create a system of "external and internal anchors" that keep the patient from committing a suicidal act. It was based on several basic questions-constructs, the answers to which could be obtained in the process of a doctor / psychologist-patient dialogue. Thus, an individual scheme of psychotherapeutic treatment was built, the purpose of which is to keep a person from a suicidal attempt. So, four basic questions: "What?", "Who?", "What?" and "How?". The article also presents a specially developed author’s scale (A.B) *, which is called the "suicidal ruler", BARS-2000 (Rapid Active Calculation of Suicidality), which was successfully used not only in the admission rooms of psychiatric hospitals for the civilian population, but also for checking persons, noncommissioned officers of the conscript service of the Israel Defense Forces.